PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR EKONOMI MATERI INFLASI PADA SISWA (KELAS XI IPS 2 SMAN 1 CARIU KABUPATEN BOGOR TAHUN PELAJARAN 2018/2019) - Deli Windrati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2022)
This classroom action research aims to improve the economics learning outcomes of Inflation material in class XI IPS-2 SMAN 1 Cariu Bogor Regency through the application of discovery learning learning models. The research method used is classroom action research with four basic interrelated and continuous stages, namely Planning (Plan), Action (Action), Observation (observation), Reflection (reflection) which is designed in 2 cycles. The subjects of this study were students of class XI IPS 2 for the 2018/2019 academic year at SMAN 1 Cariu, Bogor Regency. The number of research subjects was 29 students consisting of 10 sons and 19 daughters. The results of the study concluded 1) There was an increase in economic learning outcomes on inflation material after being given a discovery learning model to class XI IPS-2 students of SMAN 1 Cariu, Bogor Regency. This can be proven by the acquisition of an average pre-cycle score of 68.8 with 44.8% completeness, increasing to 75.2 in the first cycle with 65.5% completeness, and increasing again in the second cycle with an average value of 78.4 and learning completeness 93.1%. Thus the research has been achieved or has fulfilled the completeness of learning. 2) There is an increase in student learning activities. This is evidenced by the level of student learning activity which includes aspects of activeness, attention, discipline and assignments, which have a fairly more dominant score than a score of less so that student learning activity in the first cycle is sufficient category, then in Cycle II it is known that the level of student learning activity who has a good score is more dominant compared to other scores so that student learning activity in cycle II is in good category.